Knowledge, attitude and practice about leptospirosis and stress, and seroprevalence level among reserve officer training unit members in a Malaysian Public University - Bello, Abdul-Azeez (2016)
Introduction: Leptospirosis is a worldwide zoonotic disease. The annual incidence of the disease varies across the globe and it is more common in tropical region. Pasukan Latihan Pegawai Simpanan (PALAPES) are chosen for this study since their activities involved rigorous military exercise which can expose them to leptospiral infection from the environment. Objective: To determine the seroprevalence and the level of knowledge, attitude and practice on leptospirosis as well as stress among PALAPES in UPM. Methodology: A cross sectional study was conducted among 131 PALAPES. The study was conducted from September, 2014 to September 2015. PALAPES are students of UPM who were enrolled in to the military training during their stay on the university campus. Simple random sampling was conducted using computer generated random number of three digits. Information about the socio-demographic characteristics, knowledge, attitude and practice with the stress level were obtained using self-administered validated questionnaire in both English and Malay. Finally, five ml of blood samples were collected from the students and the samples were investigated for antibodies against leptospirosis in the laboratory. Microscopic agglutination test (MAT) was used to test against 12 serovars, using the 1:20, 1:40,1:50,1:100,1:200 and 1:400 dilution. The tested serovar were Batavae, Pomona, Hardjobovis, Canicola, Icterohaemorrhagiae, Grippotyphosa, Australis, Autumnalis, Tarasovvi, Hebdomadis, Javanica, Celledoni. In addition, strain of Sarawak and Terengganu were also tested. More so, ELResult: The response rate of this study was 72.8%, majority of the respondent (71%) were female with the mean age of 19.95 (±1.27) years and most of them were Malays (91.6%). The study had found that there was high level of knowledge, good attitude and positive practice 50.4%, 50.4% and 48.1% respectively. There was considerable high level of stress 51.1% among the students. Furthermore, there was a significant association between student years of enrolment into PALAPES with the attitude ( 0.045), there was a significant association between student year of enrolment into PALAPES with the practice ( 0.001) and there was a significant association between student year of enrolment into PALAPES with the stress level ( 0.047). All the samples that were tested against the 12 serovars and two strains were found to be negative of titre ≥1:100. However, 2 samples were found to be positive at titre 1:50 and is an indication of past or recent exposure to the infection of Hardjobovis and Canicola. The entire samples tested with the ELISA kit were found to be negative. Conclusion: The study had found there was high level of knowledge attitude, practice and stress among the study population. There was Zero seroprevalence among the study groupISA technique was conducted using a kit from CUSABIO.